2020
DOI: 10.6018/turismo.426131
|View full text |Cite
|
Sign up to set email alerts
|

Aeropuertos inteligentes: aceptación de la tecnología por parte de los pasajeros

Abstract: En este trabajo se analiza la aceptación de las tecnologías que hacen de un aeropuerto un Aeropuerto Inteligente, por parte de los pasajeros españoles. En concreto, se comprueba cómo el uso de tecnologías autoservicio en los procesos de embarque, obtención de etiquetas de equipaje y facturación del equipaje aumenta la satisfacción del pasajero. También se muestra que el deseo de utilización de las nuevas tecnologías en estos procesos y del uso de videojuegos y pasaporte biométrico está relacionada con la edad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Third, building on this literature, this study implemented specific information on the six Spanish smart destinations, such as the year which were designed as a STD, degree of compliance rate, DMO's website and the main airport of each STD (see (Gehlot & Singh, 2022;Zamorano et al, 2020). The personalisation of the products and services rendered by air transport and hotel sectors is particularly linked to tourists' experience at STDs (Ballina, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, building on this literature, this study implemented specific information on the six Spanish smart destinations, such as the year which were designed as a STD, degree of compliance rate, DMO's website and the main airport of each STD (see (Gehlot & Singh, 2022;Zamorano et al, 2020). The personalisation of the products and services rendered by air transport and hotel sectors is particularly linked to tourists' experience at STDs (Ballina, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…We selected in this research the number of passenger arrivals (Florido-Benítez, 2023a, 2023b), hotel and room indicators (Ndou et al, 2023; Perić et al, 2022) and hotel occupancy rate indicators (Benítez-Aurioles, 2022a) because these are the most frequently used measures of tourism demand and supply. Aguirre et al (2023) note that the number of hotel and room, hotel occupancy rate and passenger and tourist arrival indicators are necessary to measure the sustainability in STDs (Gehlot & Singh, 2022; Zamorano et al, 2020). The personalisation of the products and services rendered by air transport and hotel sectors is particularly linked to tourists’ experience at STDs (Ballina, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a different research direction on eye-tracking biometric analysis technology, Morosan (2018) analyzed how positive and negative emotions influence travelers' perceptions of security through an analysis based on equity and emotion theories, and by using data from 511 US air travelers, found that perceptions of safety and the benefits of disclosure had a major impact on disclosure, while positive and negative emotions influenced travelers' perceptions of safety. Zamorano et al (2020) define the concept of a "smart airport" and analyze the acceptance of technologies at such airports, focusing on the ages of passengers and their relationship with the use of technologies. They propose a model of technology acceptance based on perceived usefulness and ease of use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is a paucity of literature that specifies the technologies included in the Smart Airport concept. In the aviation industry, various organizations have suggested the adoption of technologies, and members of the Airport Council International acknowledge the advantages of implementing biometrics to simplify, streamline, and enhance the passenger travel experience (Zamorano et al, 2020). According to ACI (2021) New technologies and digitalization have the potential to address airport capacity challenges in new ways, aiding in the recovery of pre-pandemic levels of air traffic.…”
Section: Smart Airport Conceptmentioning
confidence: 99%